Radial Nerve Palsy as an Iatrogenic Complication of Shoulder Replacement Surgery With Significant Bone Loss of the Humerus Resembling Gorham–Stout Disease: Case Report and Review of the Literature - Lisa B. E. Shields; Vasudeva G. Iyer; Yi Ping Zhang; Christopher B. Shields (Case Reports in Neurological Medicine)
Gorham–Stout disease (GSD), also known as vanishing bone disease or massive osteolysis, is a rare entity characterized by destruction of the osseous matrix and proliferation of vascular structures resulting in bone resorption. While neurological complications such as cerebrospinal rhinorrhea secondary to cranial involvement and paraplegia from spinal involvement have been reported, peripheral nerve complications are not known. We describe a case of radial nerve palsy that was an iatrogenic complication of shoulder replacement surgery with bone loss of the humerus resembling GSD. A 71-year-old male with a history of left total shoulder arthroplasty followed by a revision reverse total shoulder arthroplasty noted a “bone protruding” and pain in the left upper arm 12 years later. X-rays showed that the proximal portion of the humerus was not detectable. CT scan of the left upper extremity revealed loosening of the humeral component with prominent osteolysis most pronounced around the distal stem. The patient underwent a revision of the reverse total shoulder arthroplasty with replacement of the humeral head and shaft. He experienced numbness, pain, and weakness of the left shoulder and arm with wrist drop postoperatively. Physical exam revealed marked weakness of the dorsiflexors of the wrist and digits, wasting and weakness of the brachioradialis muscle, and loss of pinprick sensation of the superficial radial nerve distribution. Needle EMG showed denervation changes in the extensor digitorum communis, brachioradialis, and extensor carpi radialis longus muscles. An ultrasound (US) study showed enlargement of the left radial nerve at the spiral groove. The EDX and US findings suggested a left radial nerve palsy at the spiral groove. There were minimal EMG abnormalities in the deltoid and triceps muscles suggesting additional involvement of the posterior cord of the brachial plexus. This case illustrates the potential for iatrogenic radial nerve palsy following shoulder replacement surgery with significant bone loss of the humerus resembling GSD.